(untitled) (Semiárida, 2020)
The leaf area of field-grown oil flax (Linum usitatissimum L.) was estimated during its grown-vegetative and reproductive development-by means or several indirect methods. Leaf area positively and significantly (P <0,01) correlated with leaf length and width, with product of these dimensions, with leaf fresh and dry weights. and with ellipse-shaped leaf surface, according to the simple linear regression analyses.